The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s00464-018-6400-0
|View full text |Cite
|
Sign up to set email alerts
|

Early versus delayed laparoscopic cholecystectomy for acute cholecystitis: an up-to-date meta-analysis of randomized controlled trials

Abstract: ELC appears as safe and effective as DLC for acute cholecystitis within 7 days from presentation and may shorten the total hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 48 publications
0
49
0
1
Order By: Relevance
“…These findings are similar to many studies in the literature, but in these studies, it was seen that the patients in the late group operated between 8 days and 12 weeks. [17,18,[21][22][23][24] In one retrospective study, it is shorter in the early cholecystectomy group. [16] A meta-analysis study involving fifteen randomized controlled trials reported that the operative time in the early cholecystectomy group (seven days following symptom onset) was significantly longer.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…These findings are similar to many studies in the literature, but in these studies, it was seen that the patients in the late group operated between 8 days and 12 weeks. [17,18,[21][22][23][24] In one retrospective study, it is shorter in the early cholecystectomy group. [16] A meta-analysis study involving fifteen randomized controlled trials reported that the operative time in the early cholecystectomy group (seven days following symptom onset) was significantly longer.…”
Section: Discussionmentioning
confidence: 98%
“…The time limit for early LC is defined in some studies as the first 72 hours following symptom onset, [16][17][18] and in other studies, it is describe as the first 1 to 10 days. [19][20][21][22][23] Regardless of the timing of the concept of "early", all of the above-mentioned studies showed that early LC was associated with a reduction in the length of stay, workdays lost, and costs without an increase in conversion or perioperative complications. [16][17][18][19][20][21][22][23] Another important issue in the delayed group (1-8 weeks) is gallstone-related morbidity during the waiting period for a cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Los principales efectos se deben a la presión intra abdominal elevada que conduce a diversas alteraciones respiratorias, cardiovasculares y neurológicas. 2,3 Totaltrack es un dispositivo versátil, diseñado para el manejo de intervenciones previstas o inesperadas en pacientes de vía aérea difícil, incorpora un sistema de monitorización y una cámara reutilizable que se adapta rápidamente. Es el único dispositivo que permite un aporte de oxígeno a presión positiva durante la ventilación e intubación y la extubación bajo una visión continua.…”
Section: Introductionunclassified